2009
DOI: 10.21608/ejabf.2009.2044
|View full text |Cite
|
Sign up to set email alerts
|

Food and Feeding Habits of Three Cichlid Species Inhabiting Damietta Branch of the River Nile, Egypt

Abstract: ABSTRACThe present study is concerned with the seasonal analysis of the stomach contents of three species of cichlid fishes inhabiting Damietta branch of the River Nile, Egypt, namely Oreochromis niloticus (Linn., 1758), Sarotherodon galilaeus (Linn., 1758) and Tilapia zillii (Gerv., 1848). The natural food was studied from the stomach contents of fish ranging from 12-29, 11-24 and 10-21 cm in total length of the previous species, respectively. Stomach contents were analyzed using the frequency of occurrence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
2
3
0
Order By: Relevance
“…This may be attributed to the effect of low temperature on the ability of fishes to feed in the cold season. Similar results were obtained by Khallaf & Alne-na-ei (1987) about C. zillii in a Nile canal, Egypt; Shalloof et al (2009) about C. zillii in the Damietta branch of the river Nile, Egypt; Salah (2015) about O. aureus in Chybaish marsh, Iraq; Khalifa (2017) about O. aureus in Tigris river, Iraq and Mohamed & Al-Wan (2020) about C. zillii in the Garmat Ali river.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This may be attributed to the effect of low temperature on the ability of fishes to feed in the cold season. Similar results were obtained by Khallaf & Alne-na-ei (1987) about C. zillii in a Nile canal, Egypt; Shalloof et al (2009) about C. zillii in the Damietta branch of the river Nile, Egypt; Salah (2015) about O. aureus in Chybaish marsh, Iraq; Khalifa (2017) about O. aureus in Tigris river, Iraq and Mohamed & Al-Wan (2020) about C. zillii in the Garmat Ali river.…”
Section: Discussionsupporting
confidence: 70%
“…However, da Silva et al (2012) found that the high values of dietary overlaps between fish species in the Itiz river, Brazil referred to the food resource partitioning among fish species, and were associated with the abundance of these ingredients through the importance of vegetation, which is a source of conservation of the fish assemblage in the river. Shalloof et al (2009) stated that cichlid fish species did not consume food at random, but have the ability to select and choose the preferred food stuff even during different seasons. These seasonal variations in preferred food make the intraspecific competition between these species very low.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by the fact that during spawning, the fish had fully occupied abdominal cavity with the ripe gonads and empty stomach. The synchronization of the period of poor feeding activity with spawning season has been reported for other fish species (Shalloof and Khalifa, 2009). Diet composition of S. pichardus revealed that they usually feed at the surface as indicated by their planktonic stomach contents.…”
Section: Discussionsupporting
confidence: 55%
“…The results revealed that C. zillii was a highly specialized feeder, while Shep et al [63] considered C. zillii as generalized feeder in Ayamé Lake, Côte d'Ivoire6 Shalloof et al [64] stated that Cichlid fish species did not consume food at random but have the ability to select and choose the preferred foodstuff even during different seasons.…”
Section: Discussionmentioning
confidence: 99%